PENINGKATAN KETERAMPILAN MENYIMAK CERITA DRAMA DENGAN PENERAPAN PEMBELAJARAN AKTIF INOVATIF KREATIF EFEKTIF MENYENANGKAN (PAIKEM) PADA SISWA KELAS VIII-A SMPN 2 SENTAJO RAYA - Agus Riyanto (JURNAL PENDIDIKAN ROKANIA, 2020)
This research was motivated by students of class VIII-A SMPN 2 Sentajo Raya. This study aims to improve students' skills in listening to drama stories by applying PAIKEM. The method used in this study is a qualitative and quantitative description through classroom action research conducted in two action cycles. Each cycle consists of two meetings, in each meeting consisting of four meetings, namely planning, implementation, monitoring, and reflection. The results showed an increase in the competency of listening to students through the application of PAIKEM to class VIII-A students of SMPN 2 Sentajo Raya. This is evidenced by agreeing to the value of learning outcomes which shows 24 students who took the first class test totaling 9 people have not yet reached the KKM score, 15 students achieving the KKM score with a percentage of 62.50% and with an average learning result of 65.75. While in the second cycle, increasing the number of students who received the KKM value by 22 people with a percentage of 91.66% with an average value of 75.54.